Effect of gold nanocomposites treatment on male reproductive function under conditions of experimental hyperglycemia - Kaleynikova, Oksana N.; Ukrainska, Svetlana I.; Sribna, Valentine A.; Velykiy, Vasyl Y.; Vinogradova-Anyk, Alena A.; Tarasova, Katerina V.; Lagodich, Tatiana S.; Karvatskiy, Igor M.; Voznesenska, Tetyana Y.; Blashkiv, Taras V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Given the urgency of the problem of clinical and experimental pathology of diabetes mellitus (DM) and the reproductive function disorders and their correction, the direction of research was determined in the following way: to establish the functional state of testicular cells and appendages under experimental hyperglycemia, and to assess future prospects for gold nanoparticles for clinical trials. The aims to evaluate the effect of five times treatment with gold nanocomposites (gold nanoparticles (AuNPs) in the polymer matrix D-g-PAA(PE) on male reproductive function under conditions of experimental hyperglycemia. Methods: Experiments (two series) have been conducted on 120 (60 males and 60 females) Albino white laboratory mice (weighing 25-30 gm). Experimental hyperglycemia, a model of type 2 diabetes mellitus (DM2) was reproduced by administration of nicotinamide and streptozotocin (internally peritoneally). The treatment of substances was carried out in the following way: D-g-PAA (PE) (10.00 mg/kg), D-g-PAA (PE)/AuNPs (9.78 mg/kg) in the tail vein, in 0.3 ml, once a day, five times, 2 weeks after EG induction once a day, five times. Results: it was established for the first time that there is disorder of male reproductive function under conditions of experimental hyperglycemia and five-fold treatment of gold nanocomposites (D-g-PAA(PE)/AuNPs, namely an increase in the number of abnormal sperm and a decrease in spermatids, as well as an increase in preimplantation mortality of embryos (compared to this value under experimental hyperglycemia). Conclusions: Our new data suggest that treatment with such gold nanocomposites (gold nanoparticles in D-g-PAA (PE) polymer matrix) are not critical for therapeutic use (in photodynamic chemotherapy), even in hyperglycemia when there is diabetes.